Potensi Pemanfaatan Teknik Molekuler Berbasis DNA dalam Penelitian Penyakit Bulai pada Jagung: Potensi Pemanfaatan Teknik Molekuler Berbasis DNA dalam Penelitian Penyakit Bulai pada Jagung - Septian Hary Kalqutny; Syahrir Pakki; Amran Muis (Universitas Bangka Belitung, 2020)
Downy mildew is one of the major diseases in maize that may decrease maize production in Indonesia. Downy mildew in maize is caused by Peronosclerospora spp. that are obligate parasites that cannot be grown in a synthetic growth medium. Efforts to control the disease by using resistant maize varieties and fungicides often did not give the expected results, this might be due to the variations of the pathogen that have diverse nature and responses. Identification and the understanding of the biodiversity of downy mildew are major key aspects in efforts to control the disease. The Identification of species morphologically is often difficult due to the limited distinguishing characteristics and close similarities between them. Molecular biology methods are now starting to be widely used because they can provide information about the diversity of an organism genetically quickly and accurately. Therefore molecular biology methods can be used to support the morphological observations. The use of molecular markers such as RAPD, RFLP, AFLP, and SSR as well as direct sequencing of specific DNA regions (rDNA, ITS region of rDNA and mtDNA) can represent the diversity of downy mildew. In Indonesia, generally, there are three main species that cause downy mildew in maize i.e, P. philippinensis, P. maydis and P. sorghi. In the future, the use of new molecular biology techniques may provide more information faster and accurately that may be able to open more possibilities for disease control efforts.